PROSEDUR ATAS PENCATATAN KAS KECIL PADA PT. JAMINAN PEMBIAYAAN ASKRINDO SYARIAH - Rizky Arifandi Sumarsono (2021)
Petty cash is an asset in meeting the company's needs to carry out its operational activities with the simplest procedures. In its management, petty cash is carried out by the finance and accounting divisions who have the skills and expertise, as well as the importance of providing understanding to employees on matters relating to the procedures for using petty cash funds so that misuse, fraud and theft can be avoided. The purpose of writing a Final Project Report is to find out about the company's procedures for replenishing petty cash funds, recording petty cash disbursements in Microsoft Excel format, document evidence related to the process of recording petty cash disbursements by PT. Jaminan Pembiayaan Askrindo Syariah